Farm worker injuries on Western Cape fruit farms: The role of the Lay Health Worker - S Marais; A Kritzinger (AOSIS, 2005)
Aim and method: An exploratory and descriptive study to obtain basic data on the extent, nature, sources and severity of injuries sustained on fruit farms was conducted. The possibility of utilizing lay health workers (LHWs) on farms to document routine information on injuries was also investigated. Descriptive information of all injuries occurring on selected farms, both occupational and other, needing some form of treatment, were documented over a one-year period from June 1999 to May 2000. A purposive non-probability sampling method was used. Forty-eight fruit farms with a history of trained LHWs were purposefully selected. Injuries were documented using a one-page questionnaire. Results: A total of 500 injuries were recorded, giving an average of 10.4 injuries per farm per year. Half of these injuries were work-related. Workers aged 20-39 were most at risk. Injuries sustained were related to routine activities of fruit farming, occurred mostly in the orchards and involved cuts, bruises and abrasions to the hands, including the fingers, and the eyes. Most of the non-work related injuries occurred in and around the home. A third of these injuries were sustained by persons <20. A large percentage of the non-work related injuries were violence- and alcohol related. Most of the injuries required basic primary health care that could be managed by the LHW. Injury severity caused people to take time off for one third of the cases. Conclusion: A relatively high occupational injury rate in comparison to high-income countries. Occupational Health and Safety legislation needs to be institutionalized and adhered to. Alcohol and violence on farms is a serious public health problem. LHWs could potentially play an important role in documenting injury data.